DETERMINAÇÃO DE ÁCIDO SALICÍLICO EM LEITE UTILIZANDO SPOT TEST EM PAPEL E PROCESSAMENTO DE IMAGENS DIGITAIS - Josiele Aparecida Magalhães Conrado; João Flávio da Silveira Petruci (Química Nova)
Milk is a worldwide consumed product, and therefore, quality control is essential. The addition of salicylic acid (SA) represents a common type of adulteration, used to reduce the growth of microorganisms and extend shelf life. However, excessive ingestion of SA can cause gastrointestinal issues and even lead to death. This study describes the development of a simple analytical method for the determination of salicylic acid in milk based on the colorimetric reaction between the analyte and FeIII ions. The quantification was performed by digital image treatment. Different linear ranges were obtained for each type of milk analyzed: 100 to 1500 mg L-1 for raw milk, 300 to 2000 mg L-1 for skimmed milk, 500 to 2000 mg L-1 for powdered milk, 100 to 2000 mg L-1 for whole milk, and 100 to 1500 mg L-1 for lactose-free milk. The accuracy of the method was obtained by comparison with a reference method, and the recovery percentage provided values between 71 and 120%. An RSD (relative standard deviation) of 0.7% was obtained. The parameters evaluation resulted in a simple and miniaturized analytical method without a sample preparation step for the determination of SA in milk, serving as a tool for identifying adulteration practices.